Frequency of Aspirin Resistance in Ischemic Stroke Patients and Healthy Controls from Colombia - Alejandro Roman-Gonzalez; Carlos Andrés Naranjo; Walter D. Cardona-Maya; Dionis Vallejo; Francisco Garcia; Cesar Franco; Leonor Alvarez; Luis Ignacio Tobón; Marta Ibeth López; Carolina Rua; Gabriel Bedoya; Ángela Cadavid; et al. (Stroke Research and Treatment)
Objective. To evaluate the aspirin resistance prevalence in patients with previous ischemic cerebrovascular disease undergoing aspirin therapy for secondary prevention. Materials and Methods. Three hundred fifty patients presenting ischemic strokes and 100 healthy controls under aspirin treatment were evaluated using the optic platelet aggregation test. Results. Aspirin resistance was found in 7.4% of the patients with ischemic stroke and 4% of controls. Aspirin resistance was associated with stroke recurrence in univariate analysis (p=0.004). Aspirin resistance was not associated with smoking, diabetes, or hypercholesterolemia. Conclusion. Aspirin resistance is present in Colombian patients with ischemic stroke as well as in healthy controls.